RETRACTED: Characteristics of cognitive function in patients with cerebellar infarction and its association with lesion location - Liu, Qi; Liu, Chang; Zhang, Yumei (Frontiers in Aging Neuroscience, 2022)
Objective: This study aimed to explore the characteristics of cognitive function in patients with cerebellar infarction and its association with lesion location. Methods: Forty-five patients with isolated cerebellar infarction were collected in the Department of Neurology, Beijing Tiantan Hospital. Thirty healthy controls were recruited matched by age and education. Global cognitive function was evaluated by using Addenbrooke’s Cognitive Examination version III (ACE-III). An extensive neuropsychological assessment battery was also tested to evaluate the characteristics of each cognitive domain. 3D slicer software was used to draw the lesion, and evaluate the lesions’ volume, side, and location. Group analysis was used to compare the differences in cognitive performance between patients and healthy controls, and patients with left and right cerebellar hemisphere infarction. Spearman analysis was used to explore the correlation between cognitive function and lesion volume. We also subdivided each patient’s lesions according to the cerebellar atlas to identify the specific cerebellar location related to cognitive decline. Results: Patients with cerebellar infarction had a lower ACE-III score compared with the healthy group (87.9±6.2 vs. 93.7±2.9, p<0.001), and twenty-two (48.9%) patients were diagnosed with cognitive impairment. The z-transformed score of attention and executive function in the patients’ group was -0.9±1.4 and -0.8±1.0 respectively, with nineteen (43.2%) and twenty-three (56.4%) patients impaired. Compared with healthy controls, the relative risk ratio with 95% confidence interval (CI) for impairment in attention and executive function were 3.24 (1.22-8.57) and 3.39 (1.45-7.89). However, only ten (22.1%) patients showed impairment in more than two cognitive domains. Compared with the left lesion group, patients with right cerebellar infarction showed significantly impaired executive function (-1.1±0.3 vs. -0.5±0.2, p=0.01). And the cerebellar posterior lobe regions, especially lobules VI, VIII, and IX, were explored to have lower cognitive performance. Furthermore, lesion volume was identified to be associated with the ACE-III score (r=-0.37，p=0.04). Conclusion: We identified that cerebellar involvement in cognition, especially in attention processing and executive function. Cerebellar right-sided lateralization of cognition and functional topography were also revealed in the current study.